Post-hoc analysis from phase III trials of human papillomavirus vaccines: considerations on impact on non-vaccine types. (4th March 2019) - Ryser, Martin; Berlaimont, Valérie; Karkada, Naveen; Mihalyi, Attila; Rappuoli, Rino; van der Most, Robbert
ABSTRACT: Background : Substantial heterogeneity has been reported in efficacy against high-grade cervical intraepithelial neoplasia (CIN) irrespective of HPV type in phase III results for bivalent and quadrivalent human papillomavirus virus (HPV) vaccines (AS04-HPV and qHPV). Real-world data recently confirmed a very high overall impact of AS04-HPV, supporting the validity of the observed heterogeneity. To explore the reasons for heterogeneous efficacy, we assessed vaccine impact on high-grade lesions not caused by vaccine types. Research methods : We extracted case counts of CIN lesions containing (1) at least one vaccine HPV type, (2) at least one vaccine HPV type and a high-risk non-vaccine type (co-infections) and (3) no vaccine types (non-vaccine or no high-risk HPV types). Based on these, Phase III cross-protective efficacies were estimated with exclusion (3) and with inclusion (2 and 3) of co-infections. Results : Cross-protective efficacy of AS04-HPV against CIN3 lesions ranges from 81.3% (95%CI: 34.7;96.5) (excluding co-infections) to 88.5% (95%CI:62.4;97.8) (including co-infections). For qHPV the efficacy ranges from −58.7% (95%CI: −180.5;8.5) (excluding co-infections) to 13.1% (95%CI: −39.0;45.9) (including co-infections). Conclusions : Heterogenous overall efficacy against CIN3 between AS04-HPV and qHPV is driven by differential efficacy against lesions that do not contain vaccine types, which may be related to the impact of different adjuvants on the immune response.